1433. Association Between Impact of Pneumococcal Conjugate Vaccines (PCVs) on Acute Respiratory Infections Rates and Impact on Antibiotic Consumption Rates in Young Children. (26th November 2018) - Dagan, Ron; Danino, Dana; Ben-Shimol, Shalom; Greenberg, David; Givon-Lavi, Noga
Abstract: Background: Acute respiratory infections (ARIs) are the main reason for prescribing antibiotics in young children. The impact of PCVs on ARIs is well documented. We attempted to assess the post 7- and 13-valent PCVs (PCV7/PCV13) temporal relationship of reduction in ARI rates vs. reduction in rates of dispensed antibiotic prescriptions (DAPs) in community clinics for children < 2 years old. Methods: Most children in the Southern Israel district belong to the Clalit Health Maintenance Organization (Clalit-HMO), where all dispensed antibiotics are computerized. We enrolled all Clalit-HMO pediatric clinics in southern Israel that: (1) had ≥50 insured children < 2 years; and (2) were active both before and after PCV implementation. In the years 2005–2009, an average of 22, 187 children < 2 years were insured yearly by the Clalit-HMO. PCV7/PCV13 were implemented in July 2009/November 2010, respectively, and rapidly reached ≥90% coverage. To associate post-PCV DAP to ARI rate dynamics, we used three separate population-based databases on ARIs (table). Over 95% of births and medical services in the southern Israel district take place at the only medical center in the district, enabling incidence calculation. Dynamics of incidences and incidence rate ratios (IRRs) were calculated, using the population at risk for each year. Results: Incidence rates (Figure 1) and IRRs (Figure 2) for otitis media, acute purulent conjunctivitis, chest radiographies for ARI in pediatric emergency room showed similar, but not identical trends compared with DAP rate trends: All incidences were significantly reduced, especially after PCV13 implementation. This resulted in a 25.6% reduction of DAPs. Extrapolated to a cohort of 100, 000 births, translates into a saving of 140, 419 (95% CI 133, 837–146, 453) prescriptions through the first 2 years of life. Conclusion: The temporal association between ARI and DAP rate dynamics suggests a causative relationship. We speculate that reduction of ARIs led to reduced clinic visits and hence decline in antibiotic prescriptions. Disclosures: R. Dagan, Pfizer: Consultant, Grant Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Grant recipient, Research grant and Speaker honorarium; MeMed: Consultant, Consulting fee; MSD: Consultant, Grant Investigator and Scientific Advisor, Consulting fee and Research grant. S. Ben-Shimol, Pfizer: Grant Investigator and Speaker's Bureau, Research grant and Speaker honorarium. D. Greenberg, Pfizer: Consultant and Speaker's Bureau, Consulting fee and Speaker honorarium.